Protected Culture for Vegetable and Small Fruit Crops: Southern Highbush Blueberry Cultivars under High Tunnels - Bielinski M. Santos; Teresa P. Salame-Donoso (EDIS, 2013)
High tunnels have been proposed as an alternative for freeze protection and to increase fruit earliness of southern highbush blueberry. But there is no information about the effect of this type of structure on southern highbush blueberry fruit earliness under subtropical Florida conditions. This 3-page fact sheet summarizes the results of 2-year study in a commercial southern highbush blueberry farm in North Central Florida to compare early fruit weight in high tunnels to that of open fields. This 3-page fact sheet was written by Bielinski M. Santos and Teresa P. Salame-Donoso, and published by the UF Department of Horticultural Sciences, July 2013. http://edis.ifas.ufl.edu/hs1226